Catalogue of Positions and Proper Motions of Stars in the Vicinity of Open Clusters - Protsyuk, Yu.I.; Kovalсhuk, O.M.; Mazhaev, O.E. (Science and Innovation, 2024)
In the Research Institute Mykolaiv Astronomical Observatory (MAO) the catalogue of position and proper motions of stars in the 544 square areas of nearly (1×1)°around the Galactic open clusters was created using photographic and CCD observations. 293 plates of (5×5)°obtained with the MAO Zonal Astrograph (D=116 mm, F=2040 mm) in 1962-1993 and more than 20 thousands CCD frames (0.7×0.7)° obtained with KT-50 telescope (D=500 mm, F=3000 mm) in 2011-2015 were used. Almost 270 thousands FITS files from the IVOA image archives with observational epoch from 1953 to 2010 were downloaded and processed. The created catalogue contains more than 2.3 million stars (7.5-18.5)m in the ICRS system with the accuracy of positions on both coordinates ranged from 0.02" to 0.05". Inner accuracy of proper motions is ~0.004"/year.